2023
DOI: 10.1177/21501351221146150
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Institutional Experience with 36 Children Smaller Than 5 Kilograms Supported with the Berlin Heart Ventricular Assist Device (VAD) over 12 Years: Comparison of Patients with Biventricular versus Functionally Univentricular Circulation

Abstract: Objectives We reviewed outcomes in all 36 consecutive children <5 kg supported with the Berlin Heart pulsatile ventricular assist device (VAD) at the University of Florida, comparing those with univentricular circulation (n  =  23) with those with biventricular circulation (n  =  13). Methods The primary outcome was mortality. Kaplan-Meier methods and log-rank tests were used to assess group differences in long-term survival after VAD insertion. T-tests using estimated survival proportions and standard erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…We previously reported an analysis of neonates and infants <5 kg supported with ventricular assist device, comparing those with functionally univentricular circulation to those with biventricular circulation, and we concluded that "Pulsatile VAD facilitates bridge to transplantation in neonates and infants weighing <5 kg; however, survival after VAD insertion in these small patients is less in those with univentricular circulation in comparison to those with biventricular circulation." 23 Our current analysis complements this prior study by reanalysing this previously published dataset and comparing patients with CHD to those with acquired heart disease. This overall detailed comparison has not been published until this current manuscript.…”
Section: The Value Of This Analysismentioning
confidence: 75%
See 1 more Smart Citation
“…We previously reported an analysis of neonates and infants <5 kg supported with ventricular assist device, comparing those with functionally univentricular circulation to those with biventricular circulation, and we concluded that "Pulsatile VAD facilitates bridge to transplantation in neonates and infants weighing <5 kg; however, survival after VAD insertion in these small patients is less in those with univentricular circulation in comparison to those with biventricular circulation." 23 Our current analysis complements this prior study by reanalysing this previously published dataset and comparing patients with CHD to those with acquired heart disease. This overall detailed comparison has not been published until this current manuscript.…”
Section: The Value Of This Analysismentioning
confidence: 75%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Over the past four years, our programme has published a series of manuscripts describing our evolving approach to supporting neonates, infants, and children with ventricular assist devices. [15][16][17][18][19][20][21][22][23][24] These ten previous publications describe the evolving details of our techniques for ventricular assist device support in neonates, infants, and children with both CHD and acquired heart disease, including the use of "Single Ventricle-Ventricular Assist Device" support in patients with functionally univentricular circulation.…”
Section: Introductionmentioning
confidence: 99%